Oncofetal reprogramming and cellular plasticity in colorectal cancer: from mechanisms to clinical translation - Haoyu Wang; Songhao Liu; Mingxuan Zhang; Chunping Deng; Zhenguo Han (Frontiers in Oncology, 2026)
Colorectal cancer (CRC) progression and metastasis, as well as tolerance to therapy, are driven not only by genetic alterations but also by cell-state plasticity. Oncofetal reprogramming (OnF) refers to the reactivation of fetal intestinal developmental or injury-repair programs in tumor cells, thereby weakening adult lineage identity and enhancing the capacity for state transitions. Available evidence suggests that, in specific Wnt-dependent or APC-aberrant contexts, YAP/TAZ–TEAD and AP-1 may act cooperatively to establish and maintain the OnF state, whereas Wnt, EGFR–MAPK, FGF/FGFR, TGF-β, and extracellular matrix signaling contribute to its establishment and maintenance in a context-dependent manner. The OnF state can also intersect with epithelial–mesenchymal plasticity, dynamic stemness, drug-tolerant persister states, and immune and stromal niches, collectively increasing cellular heterogeneity, adaptability to therapy, and relapse potential in CRC. This review discusses the conceptual boundaries and operational criteria for identifying OnF in CRC, examines its regulatory mechanisms, plasticity-associated phenotypes, and translational relevance, and emphasizes the importance of distinguishing direct evidence of OnF from evidence of related plasticity mechanisms. Further elucidation of the OnF state may facilitate biomarker development and anti-plasticity therapies, although its clinical translation will require standardized state classification and clinical validation.